Locus of control and low-wage mobility - Daniel D. Schnitzlein; Jens Stephani (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
We investigate whether non-cognitive skills - in particular Locus of Control - are important determinants of the labour market processes at the low-wage margin. Based on data from the German Socio-Economic Panel, we estimate dynamic multinomial logit models with random effects and investigate whether Locus of Control influences the probability of being higher-paid or low-paid as well as the probability of escaping low wages by moving up to higher-paid employment. Our results reveal a significant amount of state dependence in low pay even after controlling for Locus of Control and other non-cognitive skills. Furthermore, compared to individuals with an external Locus of Control, individuals with a more internal Locus of Control have a significantly higher probability of being higher-paid instead of low-paid. Conditional on being low-paid, individuals with an internal Locus of Control additionally have a significantly higher probability of moving to higher-paid employment in the following year than individuals with an external Locus of Control.
Keywords: J30; J60; 330; low-wage; wage mobility; personality; non-cognitive skills; inequality; SOEP